2021
DOI: 10.1002/cam4.4045
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune‐related pneumonitis with clinical benefit of anti‐programmed cell death‐1 monotherapy in advanced non‐small cell lung cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
0
21
0
4
Order By: Relevance
“…The occurrence of irAEs indicates that immunotherapy has activated the immune system of patients. Patients with greater toxicity to immune drugs can attain better curative effects, leading to prolonged PFS and OS ( 20 ). In a meta-analysis ( 74 ), irAEs, especially endocrine, dermatologic and low-grade irAEs, were significantly associated with better ICI outcomes in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of irAEs indicates that immunotherapy has activated the immune system of patients. Patients with greater toxicity to immune drugs can attain better curative effects, leading to prolonged PFS and OS ( 20 ). In a meta-analysis ( 74 ), irAEs, especially endocrine, dermatologic and low-grade irAEs, were significantly associated with better ICI outcomes in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to the data of clinical trials, the incidence of ICI-P is 3%—6.3% in NSCLC, and the mortality rate is <1% ( 14 16 ). However, in previous epidemiological studies, the incidence of ICI-P varied greatly, ranging from 2.7% to 19% in NSCLC ( 17 20 ) ( Table 1 ). Patients with lung cancer are more likely to develop ICI-P than patients with other types of cancer ( 17 ).…”
Section: Introductionmentioning
confidence: 93%
“…The same is true with skin reactions and pneumonitis. 18 , 19 However, the reasons why the development of any irAE is associated with tumor response remain unknown. Further research is warranted to uncover the reason for this association.…”
Section: Discussionmentioning
confidence: 99%
“…In CIP patients, Suresh et al 3 demonstrated that although ICIs did not significantly affect short‐term survival including disease control rate, overall response rate, and PFS, it would decrease the overall survival(OS) by 10 months. Another study reported that CIP increased PFS and OS, and 25% of patients continued to have no tumor growth after treatment discontinuation 76 . In real world studies, CIP is associated with poor prognosis 3,9 .…”
Section: Consensus 9: the Prognosis Of Cipmentioning
confidence: 99%
“…Another study reported that CIP increased PFS and OS, and 25% of patients continued to have no tumor growth after treatment discontinuation. 76 In real world studies, CIP is associated with poor prognosis. 3 , 9 On the other hand, the efficacy of ICI in patients with irAEs has improved.…”
Section: Consensus 9: the Prognosis Of Cipmentioning
confidence: 99%